On the identity of some endemic Brassicaceae (Cruciferae) from Middle Asia - German, Dmitry A.; Lazkov, Georgy A.; Ziyodullaev, Quyoshbek O.; Madaminov, Farrukhbek M.; Beshko, Natalya Yu.; Sennikov, Alexander N.; Tojibaev, Komiljon Sh. (Phytotaxa, 2025)
The taxonomic identity and status of six species of Brassicaceae (Cruciferae), currently accepted as very narrow endemics of Middle Asia, are critically examined. Draba kuramensis represents a hybrid between D. lanceolata and D. tibetica. Draba vvedenskyi is found to be indistinguishable from D. alberti, Erysimum aksaricum is a synonym of E. marschallianum, Lepidium botschantzevii fully agrees with L. curvinervium, Lepidium uzbekistanicum is not separable from L. paniculatum, and Parrya nuratensis is identical with P. fruticulosa. A new synonymy is therefore established.